THE EFFECT OF AUDIOVISUAL MEDIA ON STUDENTS' KNOWLEDGE OF PREVENTION AND CONTROL OF DENGUE VECTORS AT SDN 105312 SAWIT REJO - Nanda, Meutia; Safira, Putri; Anggraini, Riri; Elvina, Elvina; Salsabilla, Salsabilla; Putri, Dian Yustika (HEARTY, 2025)
Dengue fever is still a significant public health problem in Indonesia. DHF prevention efforts require the active role of the community, especially elementary school students. One effective way to increase knowledge about DHF is by using audiovisual media. This study aims to determine the effect of audiovisual media on students' knowledge about dengue vector prevention and control at SDN 105312 Sawit Rejo. The research method used was an experimental design “One-Group Pretest-Posttest Design” with a sample of 50 students in grades IV and VI selected using total sampling technique. Data were collected through questionnaires and analyzed using the Wilcoxon Signed Rank Test non-parametric test. The results showed a significant increase, namely before the intervention, most students were in the category of poor knowledge (50%) and after the intervention, almost all students (98%) were in the category of good knowledge. The Wilcoxon test results resulted in a p-value of 0.000 (p<0.05), which indicates a significant effect of audiovisual media on increasing students' knowledge about the prevention and control of dengue vectors.